Effect of TiO2 Photocatalysis on the Destruction of Microcystis aeruginosa Cells and Degradation of Cyanotoxins microcystin-LR and Cylindrospermopsin - Vítor J. P. Vilar (2015)
This study assesses the effect of a solar driven TiO2 photocatalytic process on the destruction of the cyanobacteria Microcystis aeruginosa with simultaneous removal of intracellular and extracellular microcystin-LR (MC-LR) due to cell lysis. Transmission electron microscopy (TEM) was used to study the interaction between TiO2 nanoparticles and M. aeruginosa cells. Due to the cell size, TiO2 nanoparticles aggregate on the exterior surface of the cell. Cell lysis is mainly associated with cell wall attack by the reactive species formed on the semiconductor surface, leading to the release of toxins to the liquid phase. The efficiency of the solar driven TiO2 photocatalytic process was also evaluated in the treatment of natural water from a Portuguese river containing cyanobacterial blooms, in which prevails the genus Microcystis. The degradation of MC-LR, previously purified and spiked in distilled water, was assessed using a pilot scale solar photoreactor. Two degradation byproducts were identified and relative abundances were evaluated along the reaction time. The best results corresponding to the faster MC-LR and byproducts degradation were obtained with a catalyst concentration of 200 mg L-1. The best catalyst concentration found to destroy MC-LR was also used in cylindrospermopsin (CYN) toxin degradation. CYN molecule showed higher recalcitrant character than MC-LR, requiring a higher solar exposure time to achieve similar degradation efficiencies.